2021
DOI: 10.3389/fpsyt.2020.600583
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Deficit Within the Fronto-Limbic-Striatal Circuit in First-Episode Drug Naïve Patients With Major Depression Disorder

Abstract: Background: Depression is a major psychiatric disorder and the leading cause of disability worldwide. Previous evidence suggested certain pattern of structural alterations were induced by major depression disorder (MDD) with heterogeneity due to patients' clinical characteristics and proposed that early impairment of fronto-limbic-striatal circuit was involved. Yet the hypothesis couldn't be replicated fully. Accordingly, this study aimed to validate this hypothesis in a new set of first-episode, drug naïve MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The identification and attrition of the studies are shown in Figure 1 . Finally, the search identified 2,044 studies, and only 19 studies met the inclusion criteria ( 7 , 12 24 , 36 40 ), of which three reported two separate experiments ( 7 , 20 , 39 ). Our final sample consisted of 619 first-episode MDD patients (371 females and 248 males; mean age 33.43 ± 4.71 years) and 707 HCs (403 females and 304 males; mean age 32.90 ± 4.79 years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification and attrition of the studies are shown in Figure 1 . Finally, the search identified 2,044 studies, and only 19 studies met the inclusion criteria ( 7 , 12 24 , 36 40 ), of which three reported two separate experiments ( 7 , 20 , 39 ). Our final sample consisted of 619 first-episode MDD patients (371 females and 248 males; mean age 33.43 ± 4.71 years) and 707 HCs (403 females and 304 males; mean age 32.90 ± 4.79 years).…”
Section: Resultsmentioning
confidence: 99%
“…The identification and attrition of the studies are shown in Figure 1. Finally, the search identified 2,044 studies, and only 19 studies met the inclusion criteria (7,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(36)(37)(38)(39)(40), of which three reported two separate experiments (7,20,39…”
Section: Included Studies and Sample Characteristicsmentioning
confidence: 99%
“…The lingual gyrus is associated with high-level visual processing and visual memory [ 61 ]. There is significantly reduced grey matter volume in the prefrontal lobe, limbic system, striatum, lingual gyrus, and fusiform gyrus in MDD patients [ 62 ]. During emotional facial processing, grey matter structural [ 62 64 ] and functional abnormalities [ 65 ] are found in the lingual gyrus and fusiform cortices within MDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers discovered that baseline functional stability in the CAL could predict clinical symptoms improvement in depressed patients ( Li et al, 2021 ). Some neuroimaging investigations have demonstrated abnormal GM volume ( Jung et al, 2014 ; Zhang Y. et al, 2020 ), cortical thickness ( Suh et al, 2019 ; Lee et al, 2021 ) of LG and CAL in MDD patients. An earlier study found a link between visual salience and depression symptoms ( Miller et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%